Pyrethroid, Pyrroles and Neonicotinoids Insecticides Resistance on Anopheles gambiae in Keffi and Nasarawa Communities of Nasarawa State, Nigeria (Sahel Journal of Life Sciences FUDMA, 2024)
Development and spread of insecticide resistance in malaria vectors is a threat to vector control and malaria prevention efforts. This study the resistance status of pyrethroids and new insecticide classes on the survival of An. gambiae complex and their knockdown gene frequencies were determined. WHO tube tests and CDC bottle bioassays were conducted on two to five days old adult females. An. gambiae s.l. survivors were morphologically identified and species-specific identification and detection of An. gambiae s.s.  Overall, total of 3,608 An. gambiae s.l. were exposed to alphacypermethrin, deltamethrin, Chlorfenapyr and clothianidin. A total of 1,204 An. gambiae s.l. were exposed to alphacypermethrin and deltamethrin. The average mortality rate of 89.9 % (n=1134) was recorded with 10.1% (n=61) survivors in alphacypermethrin exposure and 90.7% (n=1148) with 9.3% (n=56) survivors recorded in deltamethrin exposure. A total of 600 An. gambiae s.l. were also exposed to Chlorfenapyr and clothianidin. Mortality rate due to Chlorfenapyr was 98.7 (n=596) with 1.3% (n=4) survivors while with clothianidin gave exposure mortality rates of 97.7% (n=593) with 2.3% (n=7) survivors. Analysis of survivors indicated An. gambiae s.s ranged from 80%(n=44) in Nasarawa to 86.1% (n=62) in Keffi.  Significantly, deltamethrin exposed An. gambiae (0.83 vs 0.50), Pâ‰¥0.004217 (0.50 vs 0.25, P â‰¥ 0.003892) in both Nasarawa and Keffi. Only alpha-cypermethrin exposed An. gambiae s.l. Although pyrethroid resistance was recorded in An. gambiae s.s though, malaria vectors were susceptible to both chlorfenapyr and clothianidin. Findings indicate need for deployment of new generation insecticides resistance management and malaria control programs.